2009
DOI: 10.1007/s11883-009-0061-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of circulating esterified eicosanoids and other oxylipins on endothelial function

Abstract: Eicosanoids, including epoxyeicosatrienoic acids, hydroxyeicosatetraenoic acids, and other oxylipins derived from polyunsaturated fatty acids, have emerging roles in endothelial inflammation and subsequent atherosclerosis. Unlike eicosanoids in the prostanoid series, they are known to be esterified in cell lipids such as phospholipids and triglycerides; however, our understanding of these reservoirs is in its infancy. This review focuses on recent work identifying circulating oxylipins, primarily esterified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
91
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 52 publications
1
91
0
Order By: Relevance
“…Furthermore, >90% of plasma EETs are esterifi ed to lipoprotein phospholipids in rats and humans (35)(36)(37). The direct functional role of cellular and circulating esterifi ed EETs, however, remains unclear and requires further investigation ( 34,35 ). It is important to note that free plasma oxylipins were quantifi ed in the current investigation, and that changes in circulating lipoprotein levels have been reported to impact the relative extent of oxylipin esterifi cation into lipoprotein phospholipids ( 36,37 ).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, >90% of plasma EETs are esterifi ed to lipoprotein phospholipids in rats and humans (35)(36)(37). The direct functional role of cellular and circulating esterifi ed EETs, however, remains unclear and requires further investigation ( 34,35 ). It is important to note that free plasma oxylipins were quantifi ed in the current investigation, and that changes in circulating lipoprotein levels have been reported to impact the relative extent of oxylipin esterifi cation into lipoprotein phospholipids ( 36,37 ).…”
Section: Discussionmentioning
confidence: 83%
“…Although the aforementioned cellular and physiological effects have been attributed to free EETs, and sEH rapidly hydrolyzes free EETs to their corresponding DHET metabolites, it is well-established that cellular EETs are readily esterifi ed to membrane phospholipids ( 6,34 ). Furthermore, >90% of plasma EETs are esterifi ed to lipoprotein phospholipids in rats and humans (35)(36)(37). The direct functional role of cellular and circulating esterifi ed EETs, however, remains unclear and requires further investigation ( 34,35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Error bars, S.E. diated release (62,63). Also, in this compartment, dietary EPA/ DHA supplementation resulted in a significant replacement of EETs and 20-HETE by EEQs/EDPs and 20-HEPE/22-HDoHE.…”
Section: Discussionmentioning
confidence: 86%
“…Our previous study in rats demonstrated that the shift from AA-derived CYP-epoxygenase metabolites to EPA-and DHA-derived CYP-epoxygenase metabolites occurred with largely identical effi ciencies in the plasma, heart, kidney, liver, lung, and pancreas ( 22 ). Moreover, the circulating epoxy-metabolites that are predominantly esterifi ed with lipoprotein lipids may themselves become biologically active in other tissues after being released by lipoprotein lipases ( 81 ). There is increasing evidence for a cardioprotective role of CYP-epoxygenase metabolites from studies in animal models of ischemia/reperfusion injury, maladaptive cardiac hypertrophy, and arrhythmia ( 12,24,82 ).…”
Section: Discussionmentioning
confidence: 99%